SMEs Playing in the Big Advertising League: The Transformative Potential of Programmatic Advertising and the Barriers to Its Full-Scale Implementation - Zarkada, Anna; Horstick, Marius (My University, 2025)
Programmatic advertising has emerged as a transformative digital marketing tool offering precise audience targeting, scalability, efficiency, and resource optimization through advanced technologies such individual targeting options, optimized display-ad distribution, and real-time bidding. While large corporations have widely adopted programmatic advertising, SMEs face challenges such as technical complexity, high costs, lack of expertise, and GDPR compliance. Programmatic advertising offers SMEs opportunities to optimize budget allocation and enhance advertising efficiency, yet adoption barriers including transparency concerns, infrastructure demands, and workforce limitations persist. Drawing from a synthesis of academic literature, industry reports, and direct insights from industry professionals, including marketing and advertising decision-makers from SMEs as well as high-level agency executives, we highlight both the benefits and challenges of PA adoption for European SMEs. A Four-Phase Framework is proposed to guide SMEs through analysis, planning, execution, and evaluation of programmatic advertising, emphasizing gradual adoption, investment on technical infrastructure, and workforce training. Overcoming operational and regulatory hurdles is essential to unlocking PA’s full benefits and ensuring sustainable competitiveness in the evolving digital advertising landscape.